AGRIBUSINESS STUDY OF ARTIFICIAL AND NATURAL VEGETATIVE PROPAGATION IN OPTIMIZING THE ECONOMIC VALUE OF NUTMEG PLANT PROPAGATION IN FAKFAK REGENCY - Petrus oktavianus H; Maryati (CV. Radja Publika, 2026)
The purpose of this study was to conduct an agribusiness study on the effectiveness of artificial vegetative propagation techniques in nutmeg propagation and to compare the economic efficiency of nutmeg farming between natural and artificial vegetative nursery methods. Fakfak Regency is the largest producer of nutmeg, and this has long been recognized as reflected in its nickname as the “Nutmeg City.” Proper cultivation practices are one of the keys to success in farming, where cultivation plays an important role in crop productivity, especially in providing superior seedlings. One propagation technique considered a solution is artificial vegetative propagation methods such as marcotting, budding, and top grafting. These methods are expected to produce plants identical to the parent plant in terms of superior genetic traits, early fruiting, and uniformity, with the potential for high productivity. Most nutmeg plantations in Fakfak Regency still apply natural (generative) propagation systems. This study used a quantitative method with a comparative approach to compare the effectiveness of natural and artificial nutmeg nursery methods in terms of growth, productivity, and economic efficiency. After identifying significant differences, the study continued with an agribusiness analysis of the upstream agribusiness subsystem and nutmeg farming using financial analysis methods: R/C Ratio and Net Income. The results showed that artificial vegetative methods had better success rates and growth than generative methods. Vegetative seedlings demonstrated faster and more uniform shoot growth, plant height, and leaf number. Economically, the generative method produced an R/C ratio of 1.42 with a net profit of IDR 14,750 per seedling, while the vegetative method produced an R/C ratio of 1.60 with a net profit of IDR 28,250 per seedling. This indicates that although the initial cost of vegetative propagation is higher, the resulting profit and added value are also greater. Overall, the study concluded that artificial vegetative propagation through top grafting is more effective and efficient for development in the nutmeg agribusiness system in Fakfak Regency. This method is recommended as a strategy to improve seedling quality, plant productivity, and farmers’ income, while supporting sustainable nutmeg nursery development.